Identification of a Hypothetical Protein from Podospora anserina as a Nitroalkane Oxidase - Tormos, José R. (2010)
The flavoprotein nitroalkane oxidase (NAO) from Fusarium oxysporum catalyzes the oxidation of primary and secondary nitroalkanes to their respective aldehydes and ketones. Structurally, the enzyme is a member of the acyl-CoA dehydrogenase superfamily. To date no enzymes other than that from F. oxysporum have been annotated an NAOs. To identify additional potential NAOs, the available database was searched for enzymes in which the active site residues Asp402, Arg409, and Ser276 were conserved. Of the several fungal enzymes identified in this fashion, PODANSg2158 from Podospora anserina was selected for expression and characterization. The recombinant enzyme is a flavoprotein with activity on nitroalkanes comparable to the F. oxysporum NAO, although the substrate specificity is somewhat different. Asp399, Arg406, and Ser273 in PODANSg2158 correspond to the active site triad in F. oxysporum NAO. The k(cat)/K(m)-pH profile with nitroethane shows a pK(a) of 5.9 that is assigned to Asp399 as the active site base. Mutation of Asp399 to asparagine decreases the k(cat)/K(m) value for nitroethane over two orders of magnitude. The R406K and S373A mutations decrease this kinetic parameter by 64 and 3-fold, respectively. The structure of PODANSg2158 has been determined at a resolution of 2.0 Å, confirming its identification as an NAO.